An Acute, Double‐Blind, Placebo‐Controlled Cross‐over Study of 320 mg and 640 mg Doses of Bacopa monnieri (CDRI 08) on Multitasking Stress Reactivity and Mood. (21st June 2013) - Benson, Sarah; Downey, Luke A.; Stough, Con; Wetherell, Mark; Zangara, Andrea; Scholey, Andrew
<x xml:space="preserve">Abstract</x> Little research exists in humans concerning the anxiolytic, antidepressant, sedative, and adaptogenic actions the traditional Ayurvedic medicine Bacopa monnieri (BM) possesses in addition to its documented cognitive‐enhancing effects. Preclinical work has identified a number of acute anxiolytic, nootropic, and adaptogenic effects of BM that may also co‐occur in humans. The current double‐blind, placebo‐controlled cross‐over study assessed the acute effects of a specific extract of BM (KeenMind® ‐ CDRI 08) in normal healthy participants during completion of a multitasking framework (MTF). Seventeen healthy volunteers completed the MTF, at baseline, then 1 h and 2 h after consuming a placebo, 320 mg BM and 640 mg of BM. Treatments were separated by a 7‐day washout with order determined by Latin Square. Outcome measures included cognitive outcomes from the MTF, with mood and salivary cortisol measured before and after each completion of the MTF. Change from baseline scores indicated positive cognitive effects, notably at both 1 h post and 2 h post BM consumption on the Letter Search and Stroop tasks, suggesting an earlier nootropic effect of BM than previously investigated. There were also some positive mood effects and reduction in cortisol levels, pointing to a physiological mechanism for stress reduction associated with BM consumption. It was concluded that acute BM supplementation produced some adaptogenic and nootropic effects that need to be replicated in a larger sample and in isolation from stressful cognitive tests in order to quantify the magnitude of these effects. The study was registered with the Australian and New Zealand Clinical Trials Registry (ACTRN12612000834853). Copyright © 2013 John Wiley & Sons, Ltd.